Soluble filler as a dissolution profile modulator for slightly soluble drugs in matrix tablets - Dvorácková, Katerina; Rabisková, Miloslava; Masteiková, Ruta; Muselík, Jan; Krejcová, Katerina (Drug development and industrial pharmacy, 2009)
The purpose of this experimental work was the development of hydrophilic-lipophilic matrix tablets for controlled release of slightly soluble drug represented here by diclofenac sodium (DS). Drug dissolution profile optimization provided by soluble filler was studied. Matrix tablets were based on cetyl alcohol as the lipophilic carrier, povidone as the gel-forming agent, and common soluble filler, that is lactose or sucrose of different particle size. Physical properties of tablets prepared by melt granulation and drug release in a phosphate buffer of pH 6.8 were evaluated. In vitro studies showed that used filler type, filler to povidone ratio and sucrose particle size influenced the drug release rate. DS dissolution profile could be changed within a wide range from about 50% per 24 hours to almost 100% in 10 hours. The release constant values confirmed that DS was released from matrices by the diffusion and anomalous transport. The influence of sucrose particle size on the drug release rate was observed. As the particle size decreased, the drug release increased significantly and its dissolution profile became more uniform. Soluble fillers participated in the pore-forming process according to their solubility and particle size. Formulations containing 100 mg of the drug, 80 mg of cetyl alcohol, 40 mg of povidone, and 80 mg of either lactose or sucrose (particle size 250-125 microm) were considered optimal for 24-hour lasting dissolution of DS.
Keywords: Povidone; antiflogistika nesteroidní; mastné alkoholy; velikost částic; Sucrose; Particle Size; diklofenak; Drug Carriers; Time Factors; časové faktory; pomocné látky; povidon; Solubility; tablety; rozpustnost; Anti-Inflammatory Agents, Non-Steroidal; léky s prodlouženým účinkem; Delayed-Action Preparations; Diclofenac; nosiče léků; Excipients; Lactose; Fatty Alcohols; laktosa; sacharosa; Tablets